Laparoscopic pyloromyotomy: Lessons learnt in our first 101 cases - Abhilasha Tej Handu; Vinay Jadhav; J Deepak; Jayalaxmi S Aihole; Gowrishankar; M Narendrababu; S Ramesh; K R Srimurthy (Wolters Kluwer Medknow Publications, 2014)
Aim: To analyze our experience with laparoscopic pyloromyotomy for infantile hypertrophic pyloric stenosis for the lessons that we learnt and to study the effect of learning curve. Materials and Methods: This is a retrospective analysis of case records of 101 infants who underwent laparoscopic pyloromyotomy over 6 years. The demographic characteristics, conversion rate, operative time, complications, time to first feed and post-operative hospital stay were noted. The above parameters were compared between our early cases (2007-2009) (n = 43) and the later cases (2010-2013) (n = 58). Results: 89 male and 12 female babies ranging in age from 12 days to 4 months (mean: 43.4 days) were operated upon during this period. The babies ranged in weight from 1.8 to 4.7 kg (mean: 3.1 kg). Four cases were converted to open (3.9%): three due to mucosal perforations and one due to technical problem. The mean operative time was 45.7 minutes (49.7 minutes in the first 3 years and 43.0 minutes in the next 3 years). There were 10 complications-4 mucosal perforations, 5 inadequate pyloromyotomies and 1 omental prolapse through a port site. All the complications were effectively handled with minimum morbidity. In the first 3 years of our experience the conversion rate was 9.3%, mucosal perforations were 6.9% and re-do rate was 2.3% as compared to 0%, 1.7% and 6.9%, respectively, in the next 3 years. Mean time for starting feeds was 21.4 hours and mean post-operative hospital stay was 2.4 days. Conclusion: Laparoscopic pyloromyotomy is a safe procedure with minimal morbidity and reasonable operative times. Conversion rates and operative times decrease as experience increases. Our rate of inadequate pyloromyotomy was rather high which we hope to decrease with further experience.